2023
DOI: 10.1177/15347354231178877
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Sham-Controlled Mixed Methods Pilot Study of the Feasibility of Acupuncture for Chemotherapy-Induced Neuropathy: Lessons Learned From Patient Experiences in Integrative Cancer Care

Abstract: Objective Since there is a lack of effective pharmacological therapies for chemotherapy-induced neuropathy and many patients ask for integrative cancer therapies such as acupuncture, the objective of this pilot study was to describe patients’ experiences, and to study the feasibility and short-term effects of genuine acupuncture for chemotherapy-induced neuropathic pain and unpleasant sensations compared to sham acupuncture. Methods: The pilot study used mixed methods, collecting quantitative and qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…However, it has a relatively minor role in preventing its occurrence 50 . Small sample study suggests that the effect of AC on chemotherapy‐induced peripheral neuropathy is uncertain 159 . However, studies have shown that AC can improve chemotherapy‐induced peripheral neuropathy 51–57,160 and reduce the use of analgesics 58 .…”
Section: Clinical Applications Of Acupuncture In Cancer Therapymentioning
confidence: 99%
“…However, it has a relatively minor role in preventing its occurrence 50 . Small sample study suggests that the effect of AC on chemotherapy‐induced peripheral neuropathy is uncertain 159 . However, studies have shown that AC can improve chemotherapy‐induced peripheral neuropathy 51–57,160 and reduce the use of analgesics 58 .…”
Section: Clinical Applications Of Acupuncture In Cancer Therapymentioning
confidence: 99%